DIGITAL RESTORATIVE PROCEDURES IN DENTISTRY: DIGITAL DENTISTRY - YILDIRIM, Levent (Brazilian Journal of Implantology and Health Sciences, 2024)
ABSTRACT The integration of digital technologies in restorative dentistry has significantly transformed clinical workflows, enhancing precision, efficiency, and patient outcomes. This article explores the pivotal role of various digital procedures in modern dental practices. Digital imaging techniques have revolutionized diagnostic capabilities, providing high-resolution, detailed visualizations essential for accurate treatment planning. Digital cone beam computed tomography (CBCT) has further refined diagnostic accuracy, enabling three-dimensional assessment of dental structures, which is crucial for implantology and complex restorative cases. Digital caries detection methods offer enhanced early detection of carious lesions, improving preventative care and treatment outcomes. The advent of digital impression systems has streamlined the process of capturing accurate dental impressions, reducing patient discomfort and enhancing the precision of prosthetic restorations. Additionally, digital design-manufacturing (CAD/CAM) systems have facilitated the rapid production of high-quality dental restorations, allowing for same-day procedures and greater customization. Collectively, these digital advancements are reshaping the landscape of restorative dentistry, offering unprecedented opportunities for improving the accuracy, efficiency, and overall success of dental restorations. This review aims to provide an in-depth understanding of the current state of digital restorative procedures in dentistry, with a focus on the latest technological advancements and their clinical implications. Keywords: Dentistry, digital technology, CAD/CAM, CBCT.